Caveolin-1, Ring finger protein 213, and endothelial function in Moyamoya disease. Issue 9 (December 2016) - Bang, Oh Young; Chung, Jong-Won; Kim, Suk Jae; Oh, Mi Jeong; Kim, Soo Yoon; Cho, Yeon Hee; Cha, Jihoon; Yeon, Je Young; Kim, Keon Ha; Kim, Gyeong-Moon; Chung, Chin-Sang; Lee, Kwang Ho; et al.
Background: Moyamoya disease is a unique cerebrovascular occlusive disease of unknown etiology. Ring finger protein 213 ( RNF213 ) was identified as a susceptibility gene for Moyamoya disease in East Asian countries. However, the pathogenesis of Moyamoya disease remains unclear. Methods: We prospectively analyzed clinical data for 139 patients with Moyamoya disease (108 bilateral Moyamoya disease, 31 unilateral Moyamoya disease), 61 patients with intracranial atherosclerotic stroke, and 68 healthy subjects. We compared the genetic ( RNF213 variant) and protein biomarkers for caveolae (caveolin-1), angiogenesis (vascular endothelial growth factor (VEGF) and receptor (VEGFR2), and antagonizing cytokine (endostatin)) and endothelial dysfunction (asymmetric dimethylarginine (ADMA), and nitric oxide and its metabolites (nitrite and nitrate)) between patients with Moyamoya disease and intracranial atherosclerotic stroke. We then performed path analysis to evaluate whether a certain protein biomarker mediates the association between genes and Moyamoya disease. Results: Caveolin-1 level was decreased in patients with Moyamoya disease and markedly decreased in RNF213 variant carriers. Circulating factors such as VEGF and VEGFR2 did not differ among the groups. Markers for endothelial dysfunction were significantly higher in patients with intracranial atherosclerotic stroke but normal in those with Moyamoya disease. Path analysis showed that the presence of the RNF213 variant was associated with caveolin-1 levels that could lead to Moyamoya disease. The level of combined marker of Moyamoya disease (caveolin-1) and intracranial atherosclerotic stroke (ADMA, an endothelial dysfunction marker) predicted Moyamoya disease with good sensitivity and specificity. Conclusion: Our results suggest that Moyamoya disease is a caveolae disorder but is not related to endothelial dysfunction or dysregulation of circulating cytokines.